Orchards photographed from Wire Mill - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of large orchards and homes located near Wire Mill. Mountains are visible in the background and a road is visible in between the orchards to the right of the photograph. Ladders are lying down next to the trees in the foreground.